SIMULATION ANALYSIS OF IMPACT DYNAMIC RESPONSE OF A COAL PLOW BIT - KANG XiaoMin; WANG WeiChao (Jixie qiangdu)
The plow bit is one of the key parts of the coal plow, and is the working part of the coal plow that directly contacts the coal and rock. When plowing the coal, due to the complex and tough coal seam conditions, especially when encountering hard minerals such as hard inclusions, the force on the plow bit increases sharply. The plow bit is impacted, which easily results in the failure of plow bit, such as plow bit head losing, plow bit body broken. And the consumption of plow bit is very large. Therefore, it is important to study the dynamic response of the plow bit when it is impacted during plowing. In this paper, the finite element simulation analysis method is used to conduct in-depth research on the dynamic response of the plow bit under impact. It provides theoretical references for the material selection of plow bit, the design and optimization of plow bit structure, the improvement of plow bit reliability, and the reasonable selection of the working parameters such as plow speed. It is of great significance to the design of China’s coal mining machinery and the development of coal industry.